The Subtle Signaling Strength of Smells: A Masked Odor Enhances Interpersonal Trust - van Nieuwenburg, Daan; de Groot, Jasper H. B.; Smeets, Monique A. M. (Frontiers in Psychology, 2019)
Most everyday smells, from lavender to body odors, are complex odorant mixtures that “host” particular compounds that guide (social) behavior and motivation (biomarkers). A key element of social behavior is interpersonal trust, and building on previous research showing that (i) lavender odor can enhance trust, and that (ii) certain compounds in body odor can reduce stress in mice and humans (called “social buffering”), we examined whether a grassy-smelling compound found in both body odors and lavender, hexanal, would enhance interpersonal trust. Notably, we applied odor masking to explore whether trust could be influenced subconsciously by undetectable (masked) hexanal. In Study 1 (between-subjects), 90 females played a Trust Game while they either smelled hexanal (0.01 % v/v), clove odor (eugenol: 10% v/v), or hexanal masked by clove odor (a mix of the former). As a sign of higher trust, participants gave more money to a trustee while exposed to masked hexanal (vs. the mask: eugenol). In Study 2 (within-subjects, double-blind), 35 females experienced the same three odors, while they rated the trustworthiness of a spectrum of faces that varied on trustworthiness. Controlling for subjective odor intensity and pleasantness and substantiating that masked hexanal could not be distinguished from the mask, faces were perceived as more trustworthy during exposure to masked hexanal (vs. the mask: eugenol). Whereas non-masked hexanal also increased face trustworthiness ratings, these effects disappeared after controlling for the odor’s subjective intensity and pleasantness. The combined results bring new evidence that trust can be enhanced implicitly via undetected smells.